A Transparent and Flexible Capacitive-Force Touch Pad from High-Aspect-Ratio Copper Nanowires with Enhanced Oxidation Resistance for Applications in Wearable Electronics - Kim, Dongkwan; Kwon, Jinhyeong; Jung, Jinwook; Kim, Kyunkyu; Lee, Habeom; Yeo, Junyeob; Hong, Sukjoon; Han, Seungyong; Ko, Seung Hwan (Small Methods, 2018)
Copper nanowires are widely utilized for flexible electronics applications due to their excellent electrical conductivity, mechanical flexibility, and optical transparency with very low material cost. While many previous studies are dedicated to developing effective synthesis routes for copper nanowires, most of them have focused on the control of the morphology including length and diameter rather than synthesis yields. Although many postprocessing methods have been established to make use of the copper nanowires, there still remains crucial weakness in the nanowires against oxidation stability. In this study, a new synthesis method for the morphology control of copper nanowires as well as synthesis yields is introduced. After optimizing of the copper nanowire synthesis, a copper-nanowire-based flexible transparent conductor is fabricated as a highly robust electrode by using UV-curable polyurethane acrylate resin. As a proof-of-concept, a flexible transparent capacitive-force-detection touch pad is demonstrated. The developed flexible transparent copper nanowire electrode with enhanced oxidation resistance is expected to be applied in various flexible and wearable electronics applications.
Keywords: Electrical conductivity; Electronics applications; Mechanical flexibility; Optical transparency; Oxidation stability; Polyurethane acrylates; Postprocessing methods; Transparent conductors; capacitive touch pads; copper nanowires; flexible electronics; force touch; transparent conductors